Hydrodynamic cavitation-assisted alkaline pretreatment as a new approach for sugarcane bagasse biorefineries - Terán Hilares R. (2016)
The authors gratefully acknowledge the Consejo Nacional de Ciencia, Tecnología e Innovación Tecnológica (CONCYTEC/CIENCIACTIVA-Peru, Process number 219-2014/247-2015), Conselho Nacional de Desenvolvimento Científico e Tecnológico (CNPq-Brazil, process number 449609/2014-6) and the National Research Foundation of Korea (2012M1A2A2026587) funded by the Korea government Ministry of Education, Science and Technology for financial support.